The Impact of the Snakes and Ladders Numbers Game on Early Childhood Numeracy Skills in West Bandung - Ramdani, Atep; Yuliantini, Yuliantini; Sumiati, Sumiati; Marlina, Rina (Journal of Early Childhood Education Research, 2025)
Purpose: This study aims to explore the use of the "Number Snakes and Ladders" game as an instructional medium to strengthen early numeracy skills in children aged 5–6 years at RA At-Taufiq, Bandung Barat. Methodology: This study employed a descriptive qualitative approach involving 10 children from Class B, with the classroom teacher serving as facilitator. Data were collected through participatory observation, semi-structured interviews, and documentation, then analyzed thematically following the Miles, Huberman, and Saldaña model. Results : The analysis yielded three key themes. First, from a cognitive perspective, children demonstrated notable progress in recognizing number symbols, sequencing numbers up to 50, and applying one-to-one correspondence when moving tokens according to dice rolls. Second, socially and emotionally, the game nurtured cooperation, patience, and peer support, as children encouraged one another, waited for turns, and reflected on errors. Third, motoric engagement was evident as children actively moved tokens and interacted physically with the game board, enhancing concentration and fine motor coordination. Teachers highlighted the game's adaptability, such as integrating challenge cards and visual markers, which sustained motivation and deepened conceptual understanding. Conclusions: The findings affirm that Number Snakes and Ladders can serve as an enjoyable, flexible, and developmentally appropriate medium for promoting early numeracy while simultaneously supporting socio-emotional and motoric development. In practical terms, the study provides educators with a simple yet effective strategy that can be easily adapted in classroom settings to make mathematics learning more meaningful and engaging for young children.